Preparation and Optimization of Bovine Serum Albumin Nanoparticles as a Promising Gelling System for Enhanced Nasal Drug Administration - Sandra Aulia Mardikasari; Gábor Katona; Bence Sipos; Rita Ambrus; Ildikó Csóka (Gels, 2023)
Bovine serum albumin (BSA) has been used extensively as a suitable carrier system for alternative drug delivery routes, such as nasal administration. However, the optimization of BSA nanoparticles with respect to their nasal applicability has not been widely studied. The present study focuses on the characterization of BSA nanoparticles prepared using the desolvation method, followed by a gelation process to facilitate intranasal drug delivery. The results demonstrated that the ratio of BSA and the desolvating agent, ethanol, played a critical role in the nanoparticle characteristics of the BSA nanogel matrices (BSA-NGs). Based on the gelling properties, the formulations of BSA-NG 2, BSA-NG 4, and BSA-NG 6 were selected for further investigation. The Raman spectra confirmed that there were no specific changes to the secondary structures of the BSA. The mucoadhesion studies revealed moderately high mucoadhesive properties, with a mucin binding efficiency (MBE) value of around 67%, allowing the dose to avoid elimination due to rapid mucociliary clearance of the nasal passage. Via studying the nexus of the carrier system, BSA-NGs loaded with dexamethasone as a model drug were prepared and evaluated by differential scanning calorimetry (DSC) and thermal gravimetry (TG), ascertaining that no ethanol remained in the samples after the freeze-drying process. Furthermore, the viscosity measurements exhibited moderate viscosity, which is suitable for nasal liquid preparations. The in vitro release studies performed with a simulated nasal electrolyte solution (SNES) medium showed 88.15–95.47% drug release within 4 h. In conclusion, BSA nanoparticle gelling matrices can offer potential, value-added drug delivery carriers for improved nasal drug administration.